In and out star formation in z ~ 1.5 quiescent galaxies from rest-frame UV spectroscopy and the far-infrared - Gobat, R; Daddi, E; Strazzullo, V; Garilli, B; Mignoli, M; Ma, Z; Jin, S; Maraston, C; Magdis, G; Béthermin, M; Cappellari, M; Carollo, M; et al. (EDP Sciences, 2017)
We present a sample of 34 spectroscopically confirmed BzK-selected 1011 M quiescent galaxies (pBzK) in the COSMOS field. The targets were initially observed with VIMOS on the VLT to facilitate the calibration of the photometric redshifts of massive galaxies at z and 1:5. Here we describe the reduction and analysis of the data, and the spectrophotometric properties of these pBzK galaxies. In particular, using a spatially resolved median 2D spectrum, we find that the fraction of stellar populations with ages <1 Gyr is at least 3 times higher in the outer regions of the pBzK galaxies than in their cores. This results in a mild age gradient of age 0:4 Gyr over 6 kpc and suggests either the occurrence of widespread rejuvenation episodes or that inside-out quenching played a role in the passivization of this galaxy population. We also report on low-level star formation rates derived from the [OII]3727 emission line, with SFROII 3:74:5 M yr1. This estimate is confirmed by an independent measurement on a separate sample of similarly-selected quiescent galaxies in the COSMOS field, using stacked far-infrared data (SFRFIR 24 M yr1). This second, photometric sample also displays significant excess at 1.4 GHz, suggestive of the presence of radio-mode AGN activity.